2022
DOI: 10.1002/adom.202102520
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Inorganic–Organic Luminescent Supraparticle Taggants with Switchable Dual‐Level ID

Abstract: Tracking and tracing of objects are of paramount importance for realizing a Circular Economy and can be achieved by incorporating micrometer‐scaled luminescent identification (ID) taggants. While established systems are passive, displaying merely an ID feature, for monitoring a products’ life cycle, conscious taggants with stimuli‐triggered switchable ID signals, e.g., to record a recycling step, are desired. Herein, micrometer‐scaled hybrid inorganic–organic taggants with a temperature‐triggered switchable lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 99 publications
0
4
0
Order By: Relevance
“…This processing step introduces the first level of hierarchy to the final SPs. In previous studies, [23,27,34] we exploited a versatile synthetic approach to incorporate hydrophobic coumarin dyes into thermoplastic polymer NPs via an emulsionsolvent evaporation approach utilizing sodium dodecyl sulfate (SDS) as a surfactant (schematic depiction, Figure S1, Supporting Information). [35] This approach offers an almost free choice of dye type, dye concentration, and polymer type.…”
Section: Design Of Luminescent Ratiometric Dual-threshold Temperature...mentioning
confidence: 99%
“…This processing step introduces the first level of hierarchy to the final SPs. In previous studies, [23,27,34] we exploited a versatile synthetic approach to incorporate hydrophobic coumarin dyes into thermoplastic polymer NPs via an emulsionsolvent evaporation approach utilizing sodium dodecyl sulfate (SDS) as a surfactant (schematic depiction, Figure S1, Supporting Information). [35] This approach offers an almost free choice of dye type, dye concentration, and polymer type.…”
Section: Design Of Luminescent Ratiometric Dual-threshold Temperature...mentioning
confidence: 99%
“…Pioneering examples showed that it is likely possible to control the interaction of signal carriers by assembling them into appropriate SP architectures. [54,94,95,170,173] Whether this level of interaction control can also be achieved for CSPs is, however, an open research question, which requires an in-depth investigation. If an all-rounder method to assemble all selected building blocks into CSPs with an appropriate architecture cannot be identified, combinations of different, consecutively conducted assembly methods could be exploited.…”
Section: Current Challenges and Potential Future Directionsmentioning
confidence: 99%
“…As another option, some pioneering strategies to reprogram the ID signature of a tag using external triggers without the need to extract the integrated CSPs have been described. [151,170] To realize this vision in its entirety, including the reactivation of the recorder features, however, many additional innovation cycles are required. If CSPs can neither be recovered nor reprogrammed, they should be deactivated upon exposure to specific external triggers to thereby pave the way toward fresh tagging with customized CSPs for the second use of the material.…”
Section: Envisaged Impact Of Perceptual Information-providing Matter ...mentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19][20][21][22][23] These spectral markers are promising for the development of postmortem identification (ID) tags, assuming their code-giving physical properties can withstand the harsh conditions of a fire event. [24][25][26][27] However, this is not the case for the vast majority of marking technologies relying on organic [24,[28][29][30][31][32][33][34][35] or metallic materials [22,[36][37][38][39] that either decompose or oxidize under fire conditions and lose their signaling properties. Previous work supports the assumption that inorganic Ln 3+ doped hydroxyapatite (HAp) nanowires are fire resistant.…”
Section: Introductionmentioning
confidence: 99%